Factors Related To Venous Ulceration: A Cross-Sectional Study. (October 2014) - Vlajinac, Hristina; Marinkovic, Jelena; Maksimovic, Milos; Radak, Djordje
The aim of the study was to determine the factors related to venous ulceration. Patients with venous ulceration (278 patients) were compared with 1401 patients in other categories of clinical classification of venous disease (clinical, etiologic, anatomic, and pathophysiological [CEAP]). Demographic, anthropometric, and clinical data were collected. Univariate and multivariate logistic regression analyses were used. According to multivariate analyses, risk factors for venous ulceration were age, male sex, personal history of superficial and deep venous thrombosis, diabetes, high blood pressure, skeletal or joint disease in the legs and emphysema or chronic obstructive pulmonary disease, higher body mass index and physical inactivity, parental history of ankle ulcer as well as reflux in deep and perforator veins, deep obstruction, and combination of reflux and obstruction. It seems reasonable to pay special attention to patients in whom the postulated risk factors for venous ulceration are present.